Association between Gastritis and Duodenitis with the Incidence of Hypertension in Semarang City - Yhoaninda Nurul Ilmi; Mahalul Azam; Dina Nur Anggraini Ningrum (Public Health Perspective Journal, 2026)
The prevalence rate in Semarang City has not yet reached the global SDG 2025 target of a 25% reduction (WHO, 2023). Hypertension is often referred to as a “silent killer” because its early symptoms are rarely noticeable, leading many individuals to be unaware of their condition until complications such as gastritis and duodenitis occur. This study aims to analyze the epidemiological patterns of hypertension and gastritis and duodenitis, as well as the association between these conditions and hypertension incidence. This quantitative research uses a nested case-control design with SIMPUS data from Semarang City from 2020–2022, involving 220,093 patients, consisting of 21,639 cases and 198,032 controls. The dependent variable was hypertension, while gastritis and duodenitis served as independent variables. Univariate and bivariate (chi-square) analyses were performed. The results show that hypertension was more common in women (27,709 patients) and highest in the 50–59 age group, while gastritis and duodenitis were also more frequent in women (25,042 patients), peaking in the 20–29 age group. Bivariate analysis revealed a significant association between gastritis and duodenitis and hypertension. Among males, the highest risk occurred in the 70–79 age group, with an OR of 2.76 (95% CI: 2.62–2.89), while among females, the highest risk was observed in the 80–89 age group, with an OR of 3.32 (95% CI: 3.08–3.57). The Semarang City Health Office is recommended to strengthen hypertension prevention by prioritizing early screening for gastritis and duodenitis in high-risk older adults.